2010
DOI: 10.1055/s-0030-1253576
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Transformation of Acoustic Neuroma/Vestibular Schwannoma 10 Years after Gamma Knife Stereotactic Radiosurgery

Abstract: Only a handful of cases of de-novo malignancies of the vestibulocochlear nerve have been reported. Even rarer is the malignant transformation of a previously histologically diagnosed benign vestibular schwannoma. We present the case of a young adult who had combined operative/Gamma knife treatment for a benign vestibular schwannoma, followed by further surgery 2 years later. He represented 10 years after original diagnosis with facial numbness and ataxia, MRI showing gross tumor recurrence. After radical resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 19 publications
0
33
0
3
Order By: Relevance
“…The tumor size remained stable with no sign of growth in 44.5% of the patients, decreased in 42.5%, and increased in 6.4%. Malignant transformation of intracranial schwannoma following stereotactic radiotherapy is an emerging topic in the worldwide literature [Norén, 1998;Hanabusa et al, 2001;Shin et al, 2002;Demetriades et al, 2010]. In 2011, a review of the literature by Husseini et al documented 26 cases of malignant transformation of irradiated vestibular schwannomas.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor size remained stable with no sign of growth in 44.5% of the patients, decreased in 42.5%, and increased in 6.4%. Malignant transformation of intracranial schwannoma following stereotactic radiotherapy is an emerging topic in the worldwide literature [Norén, 1998;Hanabusa et al, 2001;Shin et al, 2002;Demetriades et al, 2010]. In 2011, a review of the literature by Husseini et al documented 26 cases of malignant transformation of irradiated vestibular schwannomas.…”
Section: Discussionmentioning
confidence: 99%
“…CD11c expression is rather promiscuous, with a variety of cell types expressing this marker on their surface [38, 39]. Therefore studying the CD11c+ MHC II– cell population was difficult, as this population was heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…6,15,20 However, there is a concern that irradiation itself might play a causative role in secondary malignancy, which is a rare but a serious complication after radiation treatment, as reported in several case reports. 1,7,20,30,34 In a large study of 440 patients treated with Gamma Knife surgery for VS and with a median follow-up period of 12.5 years, the authors reported only one case of developing malignant change. The overall malignant transformation rate was calculated to 0.3%, with an annual incidence of 0.02%.…”
Section: Discussionmentioning
confidence: 99%
“…13,28 The short latency period in these cases could indicate that a malignant component already existed prior to irradiation, and might be aggravated by it, as radiation-induced malignancy usually develops over a longer period of time. 1,7,22,30 However, there is no consensus on the minimum latency period between radiation exposure and tumor development, and further work is necessary to establish a reference latency interval for radiation-induced tumors. Finally, in some case reports, patients with malignant VS have underlying NF2, a genetic condition known to be associated with a higher risk of malignant tumors, especially after radiation treatment, 2,32 and which contests Cahan's Criterion 4.…”
Section: Discussionmentioning
confidence: 99%